A comparison of the efficacy of chef knife-cleaning methods. Issue 1 (1st January 2017) - Sun, Xiaodi; Behnke, Carl; Almanza, Barbara; Nelson, Douglas
ABSTRACT: Improperly cleaned and sanitized chef knives present a potential contamination risk and a source for foodborne illness. This study compared the efficacies of two cleaning methods (three-compartment manual dishwashing and sanitizer wiping) at removing food soils from contaminated chef knives. Knife-washing procedures were standardized after observing knife-cleaning behavior in a kitchen. Adenosine triphosphate bioluminescence was used to measure levels of organic soils. Results indicated that the three-compartment manual dishwashing was more effective at removing food soils from knife surfaces than the sanitizer wiping ( P  < .0001). This study also assessed the influence of other factors on the soil removal efficacies.